SPECTROSCOPIC STUDIES OF PB(II)-SULFATE INTERACTIONS AT THE GOETHITE-WATER INTERFACE - Elzinga E.J.; Peak D.; Sparks D.L. (My University, 2001)
We used a combination of in situ attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy and X-ray absorption fine structure (XAFS) spectroscopy to conduct molecular scale studies on Pb(II)-sulfate interactions at the solid-water interface of goethite at pH 4.5, 5.0, and 6.0. Both the ATR-FTIR studies (probing sorbed SO4 in a flow cell setup as a function of the Pb concentration) and the EXAFS studies (probing sorbed Pb at high levels of co-adsorbing SO4) indicated the formation Pb-SO4 ternary complexes at the goethite surface. Based on the combined information from the IR and XAFS studies, possible Pb-SO4 ternary complex configurations were presented and discussed by comparison to a set of reference sulfate FTIR spectra. In addition to forming ternary complexes with SO4, adsorption of Pb also promoted SO4 sorption to the goethite surface by changing the surface charge, leading to additional formation of inner- and outer-sphere SO4 sorption complexes not coordinated by Pb. The relative impacts of these mechanisms (i.e., ternary complex formation versus electrostatic effects) appeared to be a function of pH and the level of Pb addition. Formation of ternary complexes was promoted (relative to the importance of electrostatic effects) at low pH values and high Pb concentrations, whereas electrostatic effects were more pronounced at high pH values and low Pb concentrations. In addition, it was found that part of the SO4 initially sorbed at the goethite surface as inner-sphere complexes without being coordinated by Pb was transformed into SO4-Pb ternary complexes as the Pb concentration was increased, an effect most pronounced at low pH. This study shows that co-adsorption of SO4 and Pb may lead to changes in both the extent and mechanisms of the adsorption of these contaminants to the goethite surface relative to binary Pb/goethite and SO4/goethite systems. The presence of co-adsorbing metals or anions may therefore significantly impact the behavior of contaminants in environmental settings.